Analysis of the Influence of Funding Sources on Salt Production Efficiency in Madura - Tunnabila, Sabna; Nugroho, Prasetyo; Purnomo, Arie Setyo Dwi (Indonesian Journal of Islamic Economics and Finance, 2024)
This research aims to analyze the influence of funding sources on the efficiency of salt production in Karanganyar Village and Pinggirpapas Village, Kalianget District, Sumenep Regency, known as the largest salt-producing area in Madura. The research population was salt business actors in Madura, totaling 880 people. The sample was determined using the Slovin formula and an error rate (standard error) of 10% (0.1), resulting in a sample of 89 respondents. Data was collected through questionnaires, interviews, and observations. Data analysis was carried out using SPSS software, and the statistical method used was a simple linear regression test. The research results show a significant positive relationship between funding sources and salt production efficiency. This can be seen from the regression coefficient of 0.101 with a p-value <0.05, which shows that the better the access to funding sources, the more efficient the salt production process will be. These findings emphasize the importance of the availability and accessibility of funding sources to increase production efficiency in the salt sector.